Impact of Debt Default, Audit Quality, Opinion Shopping and Institutional Ownership to Acceptance of Going Concern Audit Opinions - Patiran, Andarias; Marani, Yohanis; Bonsapia, Melyanus; Manginte, Shofia Y.; Noch, Muhamad Yamin (Public Policy, 2023)
This study was carried out to experimentally assess the impact of default debt, audit quality, and going concern audit opinion on those three variables. Test empirically whether institutional ownership has an impact on the going-concern audit opinion as well as the impact of shopping opinion. Concern. Data is gathered from pertinent data documentation downloaded from the website of the Indonesian Stock Exchange (www.idx.com). employing logistic regression analysis, analysed. The findings indicate a correlation between a company's likelihood of receiving a going concern audit opinion and its loan default ratio. When offering audit opinions, both big four and non-big four KAPs often maintain objectivity. The auditor will only issue a going concern audit opinion if they are concerned about the company's long-term viability. Irrespective of the given opinion, businesses frequently choose the same independent auditors.